The connecting factor of the law of the place where the damage occurs (lex loci damni) as the main conflict rule adopted in the Rome II Regulation (Discourse of Law and Administration, 2024)
The main aim of this article is to present the connecting factor of the law of place where the damage occurs (lex loci damni) as the main connecting factor used to determine the law applicable to non-contractual obligations in Regulation (EC) No 864/2007 of 11 July 2007 on the law applicable to non-contractual obligations (Rome II). Firstly, the article’s author explains what the connecting factor is, namely a criterion that helps to search for the law applicable to the factual situation described in the scope of the conflict of laws rule. Next, the connecting factor of the law of the place where the damage occurred is presented in historical and comparative approach, especially taking into account countries such as the United Kingdom, the United States and Germany. The main part of the paper is devoted to presenting the above mentioned connecting factor in the context of the Rome II Regulation by explaining the concept of damage and the place of damage, including in the jurisprudence of the CJEU.
Keywords: place where the damage occurs; damage; non-contractual obligation; connecting factor; regulation Rome II